E-scooter accidents: A rising cause of kidney injury. Issue 4 (November 2022) - Bianchi, Alberto; Gallina, Sebastian; Cianflone, Francesco; Tafuri, Alessandro; Cerruto, Maria Angela; Antonelli, Alessandro
Introduction: E-scooters recently gained mass expansion, leading to increased use-related injuries, most commonly head trauma, facial, and extremity fractures, while abdominal trauma with kidney involvement is less frequent. Here we present two cases of e-scooter-related high-grade blunt kidney trauma. Case reports: The first case was a 24-year-old male presenting with right abdominal pain after e-scooter autonomous right fall. Focused assessment with sonography for trauma (FAST) was negative, while abdominal CT showed a 3 cm middle-renal laceration. Six-day CT showed minimal urinary extravasation. Neither anemization nor impaired kidney function was observed; the patient was discharged after 9 days. The second case was a 42-year-old male presenting with right flank pain and ipsilateral chest pain after autonomous right fall. Thoracic X-ray revealed multiple rib fractures, while abdominal echography showed a non-homogeneous right kidney with a 1.5 cm perirenal fluid layer. Abdominal CT revealed 2.5 × 4 × 3.5 cm full-thickness middle-upper renal parenchyma laceration and confirmed the perirenal hematoma, while demonstrating two hepatic lesions. A series of CT and ultrasounds confirmed the stability of the aforementioned lesions and reduction of the perirenal hematoma; laboratory findings didn't show anemization nor impaired renal function. The patient was discharged after 10 days. Discussion: Widespread usage of e-scooter is accompanied by an uptick in traumatic events. The chance of renal trauma increases when lateral fall occurs. In our cases patients were hemodynamically stable, the kidney injury severity was high-grade, and non-operative management was effective. Conclusion: E-scooter accidents could lead to high-grade renal injuries, amenable of non-operative management; these events are expected to raise.